2021
DOI: 10.1186/s41610-021-00183-0
|View full text |Cite
|
Sign up to set email alerts
|

Categorized wetland preference and life forms of the vascular plants in the Korean Peninsula

Abstract: Background In 2020, a categorized list of wetland preferences, major habitats, and life forms of 4145 vascular plant taxa occurring in the Korean Peninsula was published by the National Institute of Biological Resources. We analyzed the list and explored the distribution patterns of the five categorized groups according to wetland preference, along with the information on the major habitats and the life forms of the plants belonging to those categories. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Based on Choung et al (2012) , Choung et al (2020) , Choung et al (2021) , the plants identified in the survey were assigned to the following categories according to the frequency of appearance: obligate wetland plant (OBW), facultative wetland plant (FACW), facultative plant (FAC), facultative upland plant (FACU) and obligate upland plant (OBU). Consequently, OBW accounted for 152 taxa (11.0%), FACW 138 taxa (9.9%), FAC 177 taxa (12.7%), FACU 198 taxa (14.3%) and OBU 723 taxa (52.1%) (Suppl.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Choung et al (2012) , Choung et al (2020) , Choung et al (2021) , the plants identified in the survey were assigned to the following categories according to the frequency of appearance: obligate wetland plant (OBW), facultative wetland plant (FACW), facultative plant (FAC), facultative upland plant (FACU) and obligate upland plant (OBU). Consequently, OBW accounted for 152 taxa (11.0%), FACW 138 taxa (9.9%), FAC 177 taxa (12.7%), FACU 198 taxa (14.3%) and OBU 723 taxa (52.1%) (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Listing northern lineage plants followed Gantsetseg et al (2020) , North Korean plants followed Korea National Arboretum (2019c) , endemic plants followed Chung et al (2017) and Korea National Arboretum (2020b) , rare plants and endangered wild species followed Korea National Arboretum (2009) and Korea Ministry of Environment (2021a) , respectively, floristic target plants followed Kim (2000) and National Institute of Ecology (2018) , plants in the limestone zone followed Korea National Arboretum (2010) and invasive alien species followed Chung et al (2017) and Korea National Arboretum (2019a) . The classification of wetland plants by vascular plant type followed Choung et al (2012) , Choung et al (2020) , Choung et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…The relative density, relative coverage, and frequency were calculated [ 35 ]. According to Choung et al [ 36 ], other vascular species present in the plots were classified into five categories based on the frequency of each species in its habitat as follows: obligate upland plants (OBU), facultative upland plants (FACU), facultative plants (FAC), facultative wetland plants (FACW), and obligate wetland plants (OBW). The number of fertile fronds per plot was determined in May, which is the spore season for O. cinnamomeum in Korea.…”
Section: Methodsmentioning
confidence: 99%